The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/1403494817698286
|View full text |Cite
|
Sign up to set email alerts
|

How do international medical graduates and colleagues perceive and deal with difficulties in everyday collaboration? A qualitative study

Abstract: Aim: Many medical doctors work outside their countries of origin. Consequently, language barriers and cultural differences may result in miscommunication and tension in the workplace, leading to poor performance and quality of treatment, affecting patient safety. However, there is little information about how foreign doctors and their colleagues perceive their collaboration and handle situations that can affect the quality of health services.Methods: Individual, semi-structured in-depth interviews were conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 20 publications
3
18
0
Order By: Relevance
“…An integrated review [ 23 ] found that, because of language difficulties, IENs experienced feelings of deprecation and low self-esteem. In the present study, both IENs and IMGs described how lack of language skills hindered interaction with colleagues and patients, which has also been reported by others [ 23 , 43 ]. This may be an even greater problem when learning a completely new language like Swedish as compared to English, which many people learn during school.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…An integrated review [ 23 ] found that, because of language difficulties, IENs experienced feelings of deprecation and low self-esteem. In the present study, both IENs and IMGs described how lack of language skills hindered interaction with colleagues and patients, which has also been reported by others [ 23 , 43 ]. This may be an even greater problem when learning a completely new language like Swedish as compared to English, which many people learn during school.…”
Section: Discussionsupporting
confidence: 88%
“…A Norwegian study [ 43 ] found that IMGs were reluctant to ask colleagues for support because they wanted to be seen as competent. The problem of lacking knowledge while needing to maintain one’s image at work may be problematic.…”
Section: Discussionmentioning
confidence: 99%
“…Medical culture in the scientific era may have developed an unhealthy aim of eliminating uncertainty (28). If staying in control is the overarching paradigm of the working climate you are part of, loss of control means loss of confidence from peers and represents a major threat to your position and sometimes identity (17,27,29). It probably takes repeated unpleasant emotional experiences before many physicians are able to recognize and acknowledge their own vulnerability.…”
Section: Discussionmentioning
confidence: 99%
“…As clinicians consider themselves helpers, with good intentions, patient reactions in this vein might not be understood: "why would people withdraw or become angry when I am here to help?" Of note, such reactions may also occur in collaboration between physicians, if their competency seems to be questioned (17).…”
Section: Shame In Medicinementioning
confidence: 99%
“…Empirical investigations on MPs often focus on their arrival and the early stages of recertification processes [1, 9], on educational interventions [1, 10] or on challenges, barriers and facilitating factors for workplace integration, i.e. when MPs have found employment [1, 914].…”
Section: Introductionmentioning
confidence: 99%